Conceptualizing the Competitiveness of Pharmaceutical R&D Sites A Case Study of AstraZeneca’s R&D Site in Gothenburg - Leander, Tor; Lillieroth Gan, Lukas (My University, 2025)
In the context of increasingly decentralized innovation models, understanding what makes individual pharmaceutical R&D sites competitive has become strategically important for multinational corporations. While most research on global R&D focuses on firm-level outcomes, this thesis addresses the underexplored question of how competitiveness is shaped and sustained at the level of the individual site. Through a qualitative case study of AstraZeneca’s R&D site in Gothenburg, the study investigates how internal and external factors contribute to site competitiveness within a global pharmaceutical R&D network. Drawing on 21 interviews with internal and external stakeholders, as well as written material analysis, the study explores site competitiveness as a dual construct: external competitiveness, defined by the site’s ability to deliver high-value projects to the global pipeline and internal relevance, its perceived strategic importance within the multinational corporation. The findings reveal that pipeline delivery and site perception are the key drivers of site competitiveness. These are shaped by internal success factors, such as talent, infrastructure, operations, and culture and identity, and external conditions such as ecosystem dynamics and quality of life. The study also highlights several tensions that site managers must navigate, including the balance between external competitiveness and internal relevance, the paradox of pipeline delivery, how to increase visibility without losing trust, talent loyalty and renewal, and being a builder of a local ecosystem while needing to demonstrate global value. The thesis contributes to the literature by providing a conceptual framework for understanding site-level competitiveness in pharmaceutical R&D. It offers practical insights for managers seeking to sustain relevance in an increasingly globalized innovation landscape.
Keywords: R&D site competitiveness; pharmaceutical innovation; internal relevance; external competitiveness; innovation ecosystems; multinational corporations; AstraZeneca